Involvement of Plant Stem Cells or Stem Cell-Like Cells in Dedifferentiation - Jiang, Fangwei; Feng, Zhenhua; Liu, Hailiang; Zhu, Jian (Frontiers in Plant Science, 2015)
Dedifferentiation is the transformation of cells from a given differentiated state to a less differentiated or stem cell-like state. Stem cell-related genes play important roles in dedifferentiation, which exhibits similar histone modification and DNA methylation features to stem cell maintenance. Hence, stem cell-related factors possibly synergistically function to provide a specific niche beneficial to dedifferentiation. During callus formation in Arabidopsis petioles, cells adjacent to procambium cells (stem cell-like cells) are dedifferentiated and survive more easily than other cell types. This finding indicates that stem cells or stem cell-like cells may influence the dedifferentiating niche. In this paper, we provide a brief overview of stem cell maintenance and dedifferentiation regulation. We also summarize current knowledge of genetic and epigenetic mechanisms underlying the balance between differentiation and dedifferentiation. Furthermore, we discuss the correlation of stem cells or stem cell-like cells with dedifferentiation.